CYBER SECURITY IN THE 21ST CENTURY (Ustozlar uchun, 2026)
English: In the 21st century, the rapid development of digital technologies and the widespread use of the internet have significantly increased the importance of cyber security. As individuals, organizations, and governments rely more on digital systems for communication, finance, education, and data storage, the risk of cyber threats has also grown. Cyber attacks such as hacking, phishing, malware, and identity theft can lead to serious consequences, including financial loss, data breaches, and disruption of services. This article discusses the concept of cyber security, major types of cyber threats, preventive measures, and the importance of protecting digital information in modern society.